The soil conservation agenda of Brazil: A review of “edge-to-edge” science contributions - Valera, Carlos Alberto [UNESP]; Pissarra, Teresa Cristina Tarlé [UNESP]; da Costa, Adriana Monteiro [UNESP]; Fernandes, Luís Filipe Sanches [UNESP]; Pacheco, Fernando António Leal [UNESP] (Elsevier, 2024)
Soil conservation adheres to various United Nations Sustainable Development Goals while in Brazil is a constitutional obligation. To attain the goals and fulfil the obligation, laws, policies, governance and science must be imbricated to deliver suitable conservation solutions for the long term, namely appropriate to positively influence other downstream chains such as the food chain. However, in Brazil, a major world producer and exporter of food, weaknesses were recently diagnosed by judicial authorities concerning soil governance and coordinated land use policies. Integrated scientific assessments on soil conservation and mitigation of degraded soil are also lacking in this country. This was enough motivation and the purpose to present here a holistic view over the soil conservation agenda and promoting policies in Brazil, based on a literature review that followed the guidelines and criteria of PRISMA approach. We termed this analysis a review hinged on “edge-to-edge” science contributions for two reasons. Firstly, the intent of retrieving from the recently published literature solely papers centered on a relevant soil conservation topic (e.g., soil characterization, here called an “edge”) but with complementary analyses over boundary topics (frontier “edges”, such as soil degradation). Secondly, the intent of underlining the urgency to assist decision-makers with scientific evidence in all dimensions of the soil conservation agenda (“edge-to-edge” science), namely soil characterization (e.g., quality reference values), soil degradation assessment (e.g., anthropogenic-related soil erosion or contamination), soil degradation consequences focused on the carbon cycle (e.g., net CO2 emissions and climate warming), sustainable management practices and production systems (e.g., no-tillage agriculture and integrated crop-livestock-forestry systems), and scientific evaluation of existing laws as well as of governance and policy programs with potential implications on soil quality (e.g., the Forest Code). Thus, this literature review addressed all these topics following a multidisciplinary discourse, which produced an extensive but comprehensive document about soil conservation in Brazil.
Keywords: Brazil; Integrated analysis; Land use policy; Soil conservation; “Edge-to-edge” science